Reading Strategies in Enhancing Students’ Reading Comprehension: Are They Still Relevant? - Rusgandi, Muhammad Andi (IJET (Indonesian Journal of English Teaching), 2023)
Abstract. As a result of recent technological advancements, reading in the modern period has altered in more ways than only how students interact with textbooks. However, this technological advancement really has a detrimental effect on students' reading skills. Students tend to be lazy to read books and prefer to read entertainment stuff on cell phones where the language used is mostly informal. Due to the informal language that is often used in social media and messaging apps, students were struggling with a variety of issues such as a lack of pleasure in reading, a lack of critical thinking ability, a bad reading style, and a lack of strategy, all of which contribute to their ultimate demotivation to read. This review aims to discuss theories and previous studies related to the impact of implementation of reading strategies towards students’ reading comprehension. The findings of this review show that students’ reading comprehension are positively affected by the use of reading strategies. Therefore, it is clear that reading strategies effectively contribute a prominent improvement towards the students’ reading comprehension.